Pembangunan Yang Berwawasan Lingkungan untuk Keberlanjutan Ketersediaan SDA di Masa Depan - Prasetya, Heldi (Journal Pemberdayaan Masyarakat Indonesia, 2024)
Community empowerment and development is a thing that can not be separated with each other. While the development has a close relationship with the environment. Because development is the utilization of human resources in order to cultivate and process the natural resources for the purposes of the development of the nation. The need for planning strategy and the draft integrated with attention to the perception and point of view in order to affect the implementation of the construction, that is centered on community, community participation in development, and the sustainability of environmental resources. But the construction has been done is still far from the three properties. Development is still not involving the community as well as still ignore environmental sustainability, this makes the absence of significant changes to the development of the nation. Terlebihi aspects of the sustainability of natural resources and human empowerment are not observed will affect the development and the resource itself in the future. Whereas, the human resources and natural resources are the factors determining the development of the productivity of a nation is high. On this article discusses how community empowerment can enhance the development but still pay attention to sustainability nature sustainable so don't scarcity to a loss of natural resources of the environment. Therefore that can be done to mengimplemtasikan development and empowerment of the community of environmentally sound covers the system of law enforcement environment, the role of the community, government relations, business, and society, as well as supervision and examination of the EIA on each and every development that takes place. The efforts made are also not ignore the three aspects of that civilization, economic law, and ecology.